PENERAPAN PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KESUSILAAN ANAK DIBAWAH UMUR BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 13 TAHUN 2006 TENTANG PERLINDUNGAN SAKSI DAN KORBAN - Kumara, Teguh; Kurniati, Yeti (Rechtsregel : Jurnal Ilmu Hukum, 2025)
Criminal acts of indecency against minors are serious crimes that not only cause physical injury, but also deep psychological trauma for the victims. The state is obliged to provide maximum legal protection for children as victims, as regulated in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. This study aims to examine the implementation of legal protection for child victims, as well as to examine the extent to which the regulation is effective in providing victims' rights, such as the right to physical protection, rehabilitation, restitution, and compensation. The research method used is normative juridical with a statutory approach and case studies. The results of the study indicate that although there has been a legal mechanism that regulates protection for child victims of sexual crimes, there are still obstacles in its implementation, including minimal access to legal and psychological assistance services, and limited understanding of law enforcement officers regarding the principle of the best interests of children. In conclusion, the existence of the Law on Protection of Witnesses and Victims has become an important basis in providing rights and protection for child victims of criminal acts of indecency. However, its effectiveness is highly dependent on the synergy between law enforcement agencies, LPSK, and other related parties in implementing holistic and equitable protection for children.